2018
DOI: 10.4103/jcrt.jcrt_888_17
|View full text |Cite
|
Sign up to set email alerts
|

Expert consensus statement on computed tomography-guided 125I radioactive seeds permanent interstitial brachytherapy

Abstract: The aim of this study is to develop expert consensus statement for recommendations of patient selection criteria, prescription dose, and procedure of computed tomography (CT)-guided I radioactive seeds permanent interstitial brachytherapy. Members of Chinese medical association radiation oncology branch, Chinese medical association radiation therapy professional committee, Chinese cancer society minimally invasive surgery branch seed therapy group, Chinese geriatric cancer society minimally invasive surgery br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 21 publications
0
45
0
Order By: Relevance
“…CT-guided 125 I seed implantation in the treatment of malignant tumors has been included into the treatment instruction in China, which makes this treatment more standardized [21]. In this study, from the point of exploring the long-term efficacy and safety of CT-guided 3D template-assisted 125 I seed implantation in the treatment of malignant tumors for refractory malignancies, and conducted a 2-year clinical follow-up observation, combined with post-operative verification of relevant dosimetric parameters, which further confirm the clinical efficacy and safety of the technique and the rationality of the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…CT-guided 125 I seed implantation in the treatment of malignant tumors has been included into the treatment instruction in China, which makes this treatment more standardized [21]. In this study, from the point of exploring the long-term efficacy and safety of CT-guided 3D template-assisted 125 I seed implantation in the treatment of malignant tumors for refractory malignancies, and conducted a 2-year clinical follow-up observation, combined with post-operative verification of relevant dosimetric parameters, which further confirm the clinical efficacy and safety of the technique and the rationality of the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Then CT images were uploaded into a treatment planning system. Radiation physicians outlined the gross tumor volume (GTV) on each transverse image and determined the prescription dose [according to international standards for prostate cancer and expert consensus on RIS brachytherapy (18,21)]. And the total number and activity of seed to be implanted were calculated via the modified level formula (22) (Figure 1B).…”
Section: Ct-guided Implantation Protocolmentioning
confidence: 99%
“…It is a type of low-dose-rate brachytherapy, which could deliver high radiation dose to target tumor while safely sparing the adjacent normal tissue. Previous studies indicated that 125 I brachytherapy is a feasible salvage treatment method for many cancers, including prostate cancer, lung cancer, pancreatic cancer, and head and neck cancer (18). To a certain extent, RIS implantation brachytherapy is similar to a single dose of stereotactic ablative radiotherapy and can also be called "stereotactic ablative brachytherapy" (16).…”
Section: Introductionmentioning
confidence: 99%
“…In 1999, there has been American Brachytherapy Society (ABS) recommendations for the clinical quality assurance and guidelines of permanent prostate brachytherapy with 125I 12 . In 2018, Chinses expert consensus statement on computed tomography-guided 125 I radioactive seeds permanent interstitial brachytherapy has been developed 13 .…”
Section: Case Presentationmentioning
confidence: 99%